Apolipoprotein and sphingolipid measurements: Can be used in the clinical practice of atrial fibrillation diagnosing and evaluating the cryoablation effectiveness? - Patrycja Bielawiec; Ewa Harasim-Symbor; Karolina Gołaszewska; Adrian Chabowski; Katarzyna Hodun; Klaudia Sztolsztener (PLoS ONE, 2025)
Atrial fibrillation (AF) has become the most common arrhythmia of clinical importance. A well-established and recommended therapeutic option for AF is the balloon-based cryoablation (CBA) method. There are still no sensitive biomarkers for AF prediction and cryoablation effectiveness assessment, therefore in our prospective study, we examined the plasma content of apolipoproteins (Apo) and sphingolipids, as well as the distribution of selected sphingolipids among lipoprotein fractions. The study included 33 patients with AF on admission and 24 h after cryoablation therapy, while 20 healthy volunteers were recruited to the control group. Plasma Apo concentrations were determined using a multiplex assay kit measuring fluorescence signal, whereas the high-performance liquid chromatography (HPLC) method was applied to assess the total plasma sphingolipid levels as well as their content in isolated lipoprotein fractions. Our results showed that cryoballoon ablation in AF patients markedly reduced the level of almost all Apo compared to the individuals from the control and Pre-CBA groups (Apo-A1: −25.9% and −20.0%, Apo-A2: −19.9% and −17.3%, Apo-B: −26.8% and −14.4%, Apo-C1: −20.3% and −13.4%, Apo-D: −15.9% and −22.2%, Apo-E: −18.3% and −14.3%, and Apo-J: −36.4% and −21.5%, p < 0.05, respectively). Importantly, the area under the curve of Apo-J (AUC 0.81; 95% CI, 0.71–0.92) indicates that it might be a useful biomarker of cryotherapy success in AF patients. Moreover, we also observed a pronounced increase in sphinganine (Sa; +33.5%), sphingosine (So; +24.6%), sphinganine-1-phosphate (Sa1P; +34.3%), and sphingosine-1-phosphate (So1P; +22.3%) concentrations in the Pre-CBA group in comparison with controls. This is the first study that evaluates such a broad panel of Apo and sphingolipids in patients with AF undergoing the CBA procedure, however, to confirm whether any of these parameters could be a clinically useful biomarker for predicting AF or assessing the effectiveness of treatment, further research will be necessary due to limitations of the study.